THE UNIFIED ACCOUNTING SYSTEM ACCORDING TO INTERNATIONAL ACCOUNTING STANDARDS AND FINANCIAL REPORTING, THIRD EDITION 2024 )BOOK REVIEW( - Muhannad Abbas Ayyash; Mahdi Abbas Ibadi (Scholar Express Journals, 2025)
The book is titled “Unified Accounting System in Accordance with International Accounting Standards and Financial Reporting” and was published by the Iraqi Federal Financial Supervisory Authority. It has 644 pages and is the second updated edition of 2024.
Keywords: The Unified Accounting System; International Accounting Standards; Financial Reporting